PENGARUH TEKNIK MENGAJAR DAN GAYA BELAJAR TERHADAP KEMAMPUAN BERBICARA BAHASA INGGRIS MAHASISWA POLITEKNIK LP3I JAKARTA KAMPUS CIKARANG - Euis Rabiatul Awaliah (JURNAL LENTERA AKUNTANSI, 2018)
ABSTRACTThis research entitled "The Influence Of Teaching And Learning Techniques Of English Speaking Ability Of LP3I Polytechnic Students Of Jakarta Campus Of Cikarang". The purpose of this study is to know the influence of teaching techniques and learning styles on the ability to speak english students and know the indicators of teaching techniques and learning styles that affect the ability to speak English students Polytechnic LP3I Jakarta Campus Cikarang. The method used in this research is quantitative descriptive research method. The population of this research is all students of junior profession of Polytechnic LP3I Jakarta Campus Cikarang which amounts to 100 students and sampling technique used is simple random sampling which produce sample of 40 students. Instrument used in this study is a questionnaire and along with data analysis used is simple regression. The result of this research is positive influence of teaching technique and learning style to students english speaking ability equal to 8,3%. There is a positive correlation between teaching technique and learning style to students' english speaking ability shown by correlation coefficient (R) of 0.623. Indicators of teaching techniques and learning styles have an influence on students' english speaking skills.Keywords: Teaching Technique, Learning Style, Ability to Speak